COVID-19 and Tuberculosis Vaccine - Tarro, Giulio (British Journal of Healthcare and Medical Research, 2023)
In Italy non-EU citizens were not recovered in the hospitals during the COVID-19 epidemy. They are all covered by a tuberculosis vaccine which is part of a coverage protocol provided by the Local Healthy Unit. In the Sierra de Ecuador, normally everyone received TB vaccination: the cases of manifest infection of COVID-19 are very few. In Australia tests on 4 thousand doctors and nurses with the tuberculosis vaccine took place. Lately BCG to protect against COVID-19 in health care workers has been used by many authors in clinical trials.